PENGARUH MOBILE TRUST DAN MOBILE SATISFACTION TERHADAP ELECTRONIC WORD OF MOUTH DAN NIAT MENGGUNAKAN GOPAY - Vito Lifa Meisyah Putra; Meta Andriani (Ibs Press, 2025)
This study aims to analyze the influence of Mobile Trust and Mobile Satisfaction on Electronic Word of Mouth (EWOM) and the intention to use e-wallets, focusing on the GoPay application. The method used is quantitative, with data collection through a survey questionnaire involving 100 Generation Z respondents aged 19 to 23 years. The analysis results using Partial Least Squares (PLS) indicate that Mobile Trust has a positive and significant impact on EWOM, while Mobile Satisfaction does not show a significant effect. On the other hand, Perceived Risk has been proven to positively influence the intention to use e-wallets. An interesting aspect of this hypothesis is that Generation Z tends to view high risk as a challenge. They see perceived risk not just as a barrier but as an opportunity to learn and grow, while Security significantly affects EWOM but not the intention to use e-wallets. This research underscores the importance of user trust in influencing the decision to share positive information about digital services. These findings provide insights for e-wallet service providers to develop more effective marketing strategies, focusing on enhancing Mobile Trust and service security.